1998
DOI: 10.1111/j.1600-0676.1998.tb00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Portal‐systemic encephalopathy from a spontaneous gastrorenal shunt diagnosed by three‐dimensional computed tomography and treated effectively by percutaneous vascular embolization

Abstract: Liver ISSN 0106-9543Portal-systemic encephalopathy from a spontaneous gastrorenal shunt diagnosed by three-dimensional computed tomography and treated effectively by percutaneous vascular embolization Kuramitsu T, Komatsu M, Matsudaira N, Naganuma T, Niizawa M, Zeniya A, Yoshida T, Toyoshima I, Chiba M, Masamune 0. Portal-systemic encephalopathy from a spontaneous gastrorenal shunt diagnosed by three-dimensional computed tomography and treated effectively by percutaneous vascular embolization.Abstract: A 67-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…According to our literature review, 24 cases of portosystemic encephalopathy without liver cirrhosis have been reported, including 20 from East Asia (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and four from the USA (16)(17)(18)(19), since Raskin et al reported the first case in 1964 (16). Previous studies involved mostly women (83%), with a mean age of 67.5 years (range: 37-86 years).…”
Section: Discussionmentioning
confidence: 97%
“…According to our literature review, 24 cases of portosystemic encephalopathy without liver cirrhosis have been reported, including 20 from East Asia (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and four from the USA (16)(17)(18)(19), since Raskin et al reported the first case in 1964 (16). Previous studies involved mostly women (83%), with a mean age of 67.5 years (range: 37-86 years).…”
Section: Discussionmentioning
confidence: 97%
“…Several studies used Doppler ultrasound imaging and scintigraphy to measure shunt rate and size, with many reporting the PSS to be ‘large’ or with a diameter ranging from 0·2 to 5 cm. It has been suggested that encephalopathy is not associated with PSSs, even in patients with cirrhotic livers, if the shunted fraction is less than 24–30 per cent.…”
Section: Discussionmentioning
confidence: 99%
“…Various percutaneous routes (femoral, transjugular, brachial, transhepatic, transileocolic, ileal) have been described (2,4,15). Literature reporting the radiological management of chronic portosystemic encephalopathy (CPSE) is scarce, mostly represented by small and heterogeneous series (7,8,16,17) or single case reports (9,10,14,15,19,20), mainly from Japanese authors with usually 1 year or more encephalopathy-free survival (5,8,16). Uflacker et al (18) first reported in 1987 a promising series of five patients presenting with CPSE selected for radiological interventional management.…”
Section: Discussionmentioning
confidence: 99%